The Regulation of Land Ownership Rights for Legal Entities in the Perspective of Modern Agrarian Law: Challenges of Fair Legal Evolution - Alen Saputra; Agus Yudha Hernoko; Agus Sekarmadji (Universitas Airlangga, 2026)
Land ownership is a legally recognized right that represents the strongest and most comprehensive form of control over land. Within Indonesia’s agrarian legal system, land ownership rights are fundamentally granted only to Indonesian citizens. However, in practice, certain exceptions allow legal entities to obtain land ownership rights based on Law Number 5 of 1960 concerning Basic Agrarian Principles and Government Regulation Number 38 of 1963 concerning the Designation of Legal Entities Eligible to Hold Land Ownership Rights. These provisions have sparked theoretical and philosophical debates as legal entities do not possess descendants, while land ownership is inherently hereditary. This paper examines the philosophical foundation from a normative juridical perspective regarding the granting of land ownership rights to specific legal entities, as well as the urgency of regulatory reform to ensure legal certainty and to accommodate the evolving legal and societal needs within the framework of modernization.